Boosting the overall stability of organic solar cells by crosslinking vinyl-functionalized polymer derived from PM6. (28th March 2022) - Tu, Silong; Lin, Xin; Xiao, Liren; Zhen, Hongyu; Wang, Wen; Ling, Qidan
Abstract :  Crosslinking of the vinyl-functionalized polymer (PM6-A5):Y6-based active layer can significantly boost overall stability (including thermal-stability, photo-stability, and storage-stability) of the OSCs. Abstract : In the past decade, the study on organic solar cells (OSCs) has made great progress. For commercial application, achieving high efficiency OSCs with the prominent stability is a crucial issue. Here, two crosslinkable vinyl-functionalized D–A–D–D1 -type polymers PM6-A x ( x : 5 or 15) were successfully synthesized by introducing a crosslinkable benzodithiophene (D1 ) unit with vinyl functionality into the D–A polymer PM6. As expected, the un-crosslinked PM6-A5:Y6-based OSC process an outstanding PCE (15.20%) without additives, which is higher than that of the reference PM6:Y6-based OSCs (13.65%) by the D–A–D–D1 strategy. It is found that polymers PM6-A x can be crosslinked to some extent after annealing at 150 °C for a certain period of time. Meanwhile, by thermal crosslinking of the active layer, the PM6-A x :Y6-based devices were fabricated and the stability was studied. Reference PM6:Y6-based devices were also fabricated. As a result, crosslinked PM6-A5:Y6-based devices retained 91.0% of the initial PCE under 48 h of continuous 60 °C thermal aging and 92.8% of the initial PCE under 72 h continuous white LED light illumination, whereas the reference PM6:Y6-based devices retained 81.9% and 72.7% under the same aging conditions. Moreover, crosslinked PM6-A5:Y6-based devices showed superior shelf-life stability over the reference devices. These results demonstrate that crosslinking of the PM6-A5:Y6-based active layer can significantly boost overall stability (including thermal-stability, photo-stability, and storage-stability) of the OSCs.